Patients’ Perceptions and Success Rate of Temporary Anchorage Devices After the Immediate and Delayed Loading of Orthodontic Mini-Implants-Randomized Clinical Trial - Subhrajeet Narayan Sahoo; Snigdha Pattanaik; Smruti Bhusan Nanda; Noorjahan Mohammad; Azuvi Khan; Saibalini Pani (Journal of Pharmacy and Bioallied Sciences)
Background: The search for an ideal anchorage during orthodontic treatment resulted in the invention of Orthodontic Mini Implants (OMIs) that do not require patient’s cooperation. In spite of their common use in orthodontics, there is a lack of studies regarding patients’ perceptions of OMIs after their immediate and delayed loading. Aim: The aim of this study was to compare the pain and discomfort experienced by patients following the placement of orthodontic mini-implants and immediate loading with delayed loading, and to evaluate their success rate to formulate a definite clinical protocol for loading of the orthodontic mini-implants. Material and Methods: Totally, 32 adult Orthodontic patients who required the extraction of the maxillary first premolars were recruited for the study. The use of OMIs as anchorage were randomized to immediate and delayed loading groups. A visual analogue scale questionnaire was used to seek patients’ perception about use of OMIs at different times. Success rate was also assessed using mobility and signs of inflammation around the OMIs. Results: In general, pain, swelling, bleeding, and discomfort were reported by patients more with the immediate loading group than the delayed loading group. Also, patients experienced difficulty during speech and brushing in the immediate loading group. Conclusions: From this study, it is evident that the delayed loading of the OMIs created less pain and discomfort to patients. Furthermore, the success rate of OMIs was approximately 100% in both groups.